Myotonic dystrophy type 1: clinical manifestations in children and adolescents. Issue 1 (13th January 2019) - Ho, Genevieve; Carey, Kate A; Cardamone, Michael; Farrar, Michelle A
Abstract : Objective: Myotonic dystrophy type 1 (DM1) is an autosomal-dominant neuromuscular disease with variable severity affecting all ages; however, current care guidelines are adult-focused. The objective of the present study was to profile DM1 in childhood and propose a framework to guide paediatric-focused management. Design, setting and patients: 40 children with DM1 (mean age 12.8 years; range 2–19) were studied retrospectively for a total of 513 follow-up years at Sydney Children's Hospital. 143 clinical parameters were recorded. Results: The clinical spectrum of disease in childhood differs from adults, with congenital myotonic dystrophy (CDM1) having more severe health issues than childhood-onset/juvenile patients (JDM1). Substantial difficulties with intellectual (CDM1 25/26 96.2%; JDM1 9/10, 90.0%), fine motor (CDM1 23/30, 76.6%; JDM1 6/10, 60.0%), gastrointestinal (CDM1 17/30, 70.0%; JDM1 3/10, 30.0%) and neuromuscular function (CDM1 30/30, 100.0%; JDM1 25/30, 83.3%) were evident. Conclusion: The health consequences of DM1 in childhood are diverse, highlighting the need for paediatric multidisciplinary management approaches that encompass key areas of cognition, musculoskeletal, gastrointestinal, respiratory, cardiac and sleep issues.